Body condition score (BCS), body measurement, and carcass characteristic of beef cattle in Johor Barat - Sahroni, Mohd Noranin Naim (2016)
A study was conducted to evaluate body condition score (BCS), body weight (BW), body measurements (BMs) and carcass characteristic of cattle under the small holder production system. This study used Kedah-Kelantan (KK), Brahman, cross breed and imported cattle by the farmer at Pontian Johor. The objectives of the study were to examine the quality of beef cattle related to breed type, slaughter weight and feeding management and to relate the body condition in relationship to body condition score (BCS), body weight (BW), body measurements (BMs) and carcass measurements of beef cattle from the small holder production system. A total of 31 cattle were evaluated under the small holder feedlot system. Body weight (BW), body condition score (BCS), digital photograph, body measurements (BMs), pre-slaughter weight, carcass weight, dressing percentage, marbling score, rib eye fat colour and the meat colour score were collected during the study. Four parameters of BMs collected during the study are the width of hindquarters (WQ), length of body (LB), tailhead to the hock (TH), and heart girth (HG). Others observations were made during the study such as management of the farm, feed management, and farm layout. A total of 31 cattle with a range of BCS 3 to 5 were evaluated in this study. The results in percentage are at BCS 3 (32.3%), BCS 4 (51.6%), and BCS 5 (16.1%). The highest BW of the cattle was 420 kg and the lowest BW was 135 kg, respectively. The BW highly correlated with the BCS (R2=0.828). Regression analysis between BMs and BCS of the cattle showed that LB, HG, and WQ were highly correlated at indicated by the R2 value of 0.809, 0.811, and 0.816, respectively. No BCS 1, BCS2 which is at the poor score was observed in this study and no BCS 7, BCS 8, BCS 9 which extremely fat/obese. Thus, this indicates that cattle that reared under small holder feedlot system can be reared as long as they are properly managed and provided with sufficient feed.